2023
DOI: 10.1039/d2fb00014h
|View full text |Cite
|
Sign up to set email alerts
|

Plasma processing: a sustainable technology in agri-food processing

Abstract: Overview of the different applications of plasma in pre and post-harvest processing of agri-food chain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 216 publications
0
7
0
2
Order By: Relevance
“…Within this context, resilient food processes provide the potential for entirely new and unique food product and processing concept (Barba, Tonello-Samson, et al, 2020;Barba, Parniakov, et al, 2020;Knorr & Augustin, 2022b;Rajan et al, 2023;Reineke & Mathys, 2020;Tamang et al, 2020). For example, Meinlschmidt et al (2016) also showed that the immunoreactivity of soy protein could be decreased by up to 89% when applying cold atmospheric pressure plasma.…”
Section: Resilient Food Technologiesmentioning
confidence: 99%
“…Within this context, resilient food processes provide the potential for entirely new and unique food product and processing concept (Barba, Tonello-Samson, et al, 2020;Barba, Parniakov, et al, 2020;Knorr & Augustin, 2022b;Rajan et al, 2023;Reineke & Mathys, 2020;Tamang et al, 2020). For example, Meinlschmidt et al (2016) also showed that the immunoreactivity of soy protein could be decreased by up to 89% when applying cold atmospheric pressure plasma.…”
Section: Resilient Food Technologiesmentioning
confidence: 99%
“…[38][39][40] Also, nano-research is imperative in preventing the negative effects of crop cultivation and animal farming via genetic engineering, which inadvertently increases the strength of crops and the production of farm animals. [41][42][43] Agricultural technology, including nanotools, enable stakeholders such as farmers, scientists, and policymakers to sustain agriculture through plant nutrients, nanocopper, and nano-nitrogen fertilizer production. [44][45][46] Consequently, nanotechnology adoption saves farmers money in ghting pests and diseases by enabling scientists to use microscopes to diagnose pests and diseases that are not visible before they spread to other parts of the farm.…”
Section: Nanotechnologymentioning
confidence: 99%
“…It can deal with various stages of the food and agricultural processing supply chain (i.e., preharvest and postharvest) to enhance food safety and security. In brief, plasma treatment assists in soil and water decontamination, pesticide/dye degradation, seed dormancy reduction, plant growth enhancement, insect disinfestation, bioactive extraction, enzymes/functionality/surface modifications, microbial reduction, allergen reduction, and antinutritional factor reduction . Therefore, food commodities with multiple preharvest, postharvest, and processing issues could adopt plasma technology as an alternative solution to maintain a sustainable food supply throughout the agri-food chain.…”
Section: Introductionmentioning
confidence: 99%
“…In brief, plasma treatment assists in soil and water decontamination, pesticide/dye degradation, seed dormancy reduction, plant growth enhancement, insect disinfestation, bioactive extraction, enzymes/functionality/surface modifications, microbial reduction, allergen reduction, and antinutritional factor reduction. 1 Therefore, food commodities with multiple preharvest, postharvest, and processing issues could adopt plasma technology as an alternative solution to maintain a sustainable food supply throughout the agri-food chain. In this regard, soybean was selected as the agriculture commodity with most of the above-cited pre/postharvest problems.…”
Section: Introductionmentioning
confidence: 99%